2019
DOI: 10.1039/c8bm01632a
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of enzyme-responsive growth factor nanocapsules for promoting bone repair

Abstract: Taking the advantages of the unique physiological character of bone fracture, a systemic delivery platform of growth factors for bone repair based on nanocapsules was exploited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…As a result, the formed nanocapsules sustained local GF concentration and reduced systemic side effects in rat tibial injury model. [ 98 ] Anjum et al demonstrated a modularly assembled, transglutaminase‐crosslinked poly(ethylene glycol) (TG‐PEG) and MMP Lysine‐peptide grafted chondroitin sulfate (CS) precursor (CS‐MMP‐Lys) hybrid hydrogel platform (CS‐PEG) to tune BMP‐2 binding and release to induce bone regeneration. [ 99 ] Holloway et al developed a material that concurrently delivered SDF‐1α and BMP‐2 through a hydrogel composed of a maleimide‐modified hyaluronic acid (MaHA) combined with both cell‐adhesive peptides (RGD, pendent) and MMP‐sensitive peptides (VPMS↓MRGG, crosslinker).…”
Section: Stimuli‐responsive Growth Factor Delivery Systems In Tissue mentioning
confidence: 99%
“…As a result, the formed nanocapsules sustained local GF concentration and reduced systemic side effects in rat tibial injury model. [ 98 ] Anjum et al demonstrated a modularly assembled, transglutaminase‐crosslinked poly(ethylene glycol) (TG‐PEG) and MMP Lysine‐peptide grafted chondroitin sulfate (CS) precursor (CS‐MMP‐Lys) hybrid hydrogel platform (CS‐PEG) to tune BMP‐2 binding and release to induce bone regeneration. [ 99 ] Holloway et al developed a material that concurrently delivered SDF‐1α and BMP‐2 through a hydrogel composed of a maleimide‐modified hyaluronic acid (MaHA) combined with both cell‐adhesive peptides (RGD, pendent) and MMP‐sensitive peptides (VPMS↓MRGG, crosslinker).…”
Section: Stimuli‐responsive Growth Factor Delivery Systems In Tissue mentioning
confidence: 99%
“…In addition, we have proven that proteins are not modified during polymerization. As an example, bone morphogenetic protein-2 (BMP-2) can be released from nanogels without any damage [4]. Therefore, this kind of nanogels is an excellent alternative for protein encapsulation.…”
Section: The Activity Of Native Catalase and Paam-n(catalase)mentioning
confidence: 99%
“…The protection ability of nanogels was mainly dependent on the polymeric shells formed by monomers [42,43]. Therefore, through changing the crosslinkers, we could also design the responsive-release nanogels with high protection ability to load other functional protein drugs, such as monoclonal antibodies [44] and growth factors [4], on scaffolds with organic coatings. In other words, we exploited a platform for the loading of protein drugs on scaffolds using organic coatings.…”
Section: The Detection Of the Ros Concentration In 4t1 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major shortcomings include short half‐lives in circulation, susceptibility to deactivation and degradation by enzymes, and rapid rates of internalization. [ 5,10,11 ] For example, the half‐life of vascular endothelial growth factor (VEGF) after intravenous injection is only 50 min, while that of FGF‐2 is merely 3 min. [ 5 ] This has led to the requirement of a regimen of repeated systemic administration at supraphysiologic doses, in order to achieve sustained effective local concentrations.…”
Section: Introductionmentioning
confidence: 99%